SELF-MANAGEMENT TOWARDS BULLYING PREVENTION IN ADOLESCENTS: A CROSS-SECTIONAL - Ubudiyah, Masunatul; Susanti, Inta (Journal of Vocational Nursing, 2025)
Introduction: Bullying is a health problem that often affects adolescents, especially some adolescents in schools who do not have good self-management. Self-management plays an important role in improving skills in managing students' emotions, thoughts, and behavior in a positive way to prevent bullying in adolescents. The purpose of this study was to determine the relationship between self-management and bullying prevention in adolescents. Methods: This study used a descriptive design with a cross-sectional study approach. The population in this study was students at one of the public junior high schools in Lamongan Regency who were identified as having experienced bullying in the school environment, with a total of 96 students. This study was conducted on 72 adolescents using purposive sampling. Self-management assessment used a self-management scale questionnaire for students, while bullying prevention was measured using a bullying scale questionnaire. Data were tabulated and analyzed using the Spearman Rank rho test. Results: The results of statistical tests show that self-management is related to the ability to prevent bullying in adolescents with a p-value of 0.000 and a correlation coefficient (r=0.716). Conclusions: Self-management is a key component in preventing bullying in adolescents in schools. The self-management approach requires collaboration with teachers and a positive school climate.